Toponimia indígena de Costa Rica - Quesada Pacheco, Miguel Ángel (2007)
This article gathers, analyses and studies place, river, lake and town names which descend from Costa Rican indigenous languages and are to find throughout the country. Its aim is to gather as many toponymics as possible, which are used today in Costa Rica, to find out the language that gave origin to it, and to contribute to the study of indian languages in Costa Rica.